Investigation of the relationship between upper limb apraxia and neuropsychological profile in Alzheimer's disease dementia and mild cognitive impairment - Şahintürk, Saliha; Doğanoğlu, İrem; Hanoğlu, Lütfü; Yıldırım, Erol (My University, 2024)
Objectives: This study aimed to examine the differences in upper limb apraxia assessments and neuropsychological profiles of patients diagnosed with Alzheimer's disease (AD) dementia and mild cognitive impairment (MCI) and healthy controls. Patients and methods: A total of 53 participants were included in the retrospective study, including nine patients with MCI, 23 patients diagnosed with AD, and 21 healthy patients equivalent in age and education level. The participants' data were collected between July 2021 and December 2022. A 12-question mini-test taken from the Test of Upper Limb Apraxia (TULIA) was used in the apraxia evaluation. Individuals' upper limb apraxia evaluations were compared according to diagnostic groups, and their neuropsychological profiles were also examined. Results: Apraxia was found to be associated with impairments in memory retrieval function, executive dysfunction, and decrease in object naming performance. Significant differences were observed between diagnostic groups in both apraxia assessment and neuropsychological tests. Conclusion: The findings indicate that the cognitive profile that emerges with the combined use of upper extremity apraxia assessment and related neuropsychological tests may serve as a marker and guide in the planning and correct execution of treatment in the transition to Alzheimer-type dementia, similar to other neuropsychological tests.
Keywords: Alzheimer Disease; Apraxia; Dementia; Mild Cognitive Impairment; Neuropsychology